2009
DOI: 10.5380/rsa.v10i5.15187
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogênio Em Cobertura E Molibdênio via Foliar Em Feijoeiro De Inverno No Sistema Plantio Direto.

Abstract: O nitrogênio é o nutriente absorvido em maior quantidade pelo feijoeiro e o molibdênio, além da importância no processo de fixação de nitrogênio atmosférico, está associado ao metabolismo deste nutriente. Assim, o trabalho foi desenvolvido com o objetivo de avaliar, na cultura do feijão, em sistema plantio direto, o efeito de doses de nitrogênio em cobertura (0, 30, 60, 90 e 120 kg ha-1) e de molibdênio via foliar (0, 80 e 160 g ha-1) aplicado em dois estádios de desenvolvimento das plantas (V3 e V4) no cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
0
6
0
9
Order By: Relevance
“…De qualquer forma, em diversos trabalhos, observa-se aumento de produtividade do feijoeiro com o fornecimento de molibdênio (Ferreira et al, 2003;Fernandes et al, 2005;Calonego et al, 2010;Rocha et al, 2011). As doses utilizadas têm variado em torno de 80 g ha -1 de Mo (Pessoa et al, 2000;Ferreira et al, 2003;Nascimento et al, 2009;Calonego et al, 2010) e a melhor época de aplicação situa-se em torno de 25 dias após emergência (DAE) (Pessoa et al, 2001;Ferreira et al, 2002;Calonego et al, 2010).…”
Section: Introductionunclassified
“…De qualquer forma, em diversos trabalhos, observa-se aumento de produtividade do feijoeiro com o fornecimento de molibdênio (Ferreira et al, 2003;Fernandes et al, 2005;Calonego et al, 2010;Rocha et al, 2011). As doses utilizadas têm variado em torno de 80 g ha -1 de Mo (Pessoa et al, 2000;Ferreira et al, 2003;Nascimento et al, 2009;Calonego et al, 2010) e a melhor época de aplicação situa-se em torno de 25 dias após emergência (DAE) (Pessoa et al, 2001;Ferreira et al, 2002;Calonego et al, 2010).…”
Section: Introductionunclassified
“…Fernandes et al (2005) evaluated the application of foliar Mo and N, in-furrow or sidedress, to no-tillage bean on corn stover and also found no difference for PNP. However, reports of increased PNP in response to Mo application are common in the literature (Pessoa et al, 2001;Silva et al, 2003a;Nascimento et al, 2009). For the year effect, the average PNP was higher in 2010 (Table 3).…”
Section: Resultsmentioning
confidence: 97%
“…Although there is no response pattern to Mo, the increase in yield of the bean crop with supply of Mo has been reported in a number of studies in field conditions (Araújo et al, 2009;Nascimento et al, 2009;Biscaro et al, 2011;Rocha et al, 2011). Studies prove the feasibility of fertilizer foliar application on V4 stage bean, mainly of micronutrients tank-mixed with herbicides and pesticides to reduce costs and optimize equipment usage (Araújo et al, 2008;Silva et al, 2003b).…”
Section: Introductionmentioning
confidence: 96%
“…Overall, the mean was 26.02 g, which is nearly equal to the average indicated to the BRS style, which is 26 g (CARGNIM; ALBRECHT, 2010), demonstrating that decrease of M100-induced by lack of N did not happen in any of the treatments. Nascimento et al (2009) found no relationship between nitrogen fertilization and M100, a result that can be explained by the work done by Salgado et al (2012), who studied the effect of nitrogen levels in 12 cultivars and found different responses to N doses, although only three responded to nitrogen fertilization. Fernandes et al (2005), while evaluating fertilization in the planting furrow (0 and 20 kg ha -1 ) and on coverage (0 and 70 kg ha -1 ), showed a negative effect of nitrogen fertilization on the weight of 100 grains.…”
Section: Agronomic Characteristicsmentioning
confidence: 94%